Silvopastoral system compared to other conventional production systems in the Maranhão State Cerrado - Silva, Edvan Costa da; Leonel, Léo Vieira; Reis, Fabrício de Oliveira; Catunda, Paulo Henrique Aragão; Silva, Luciana Sabini da; Menechini, Wagner (Scientia Agraria Paranaensis, 2020)
Silvipastoral systems are identified as options for land use due to the high potential they offer to increase the level of income from agronomic, social, economic, and ecological aspects. Given the above, this study aimed to evaluate the environmental benefits of implementing a silvopastoral system in Cerrado Maranhense, in comparison to other conventional production systems. The same was done in 2013 from February to May on a private property located in São Francisco do Brejão (MA) during the rainy season. The experiment evaluated three types of system: a) silvopastoral, composed of leucaena, grasses, and beef cattle, b) rotational system, and c) extensive system. A randomized block design in a 3x3 factorial scheme with three replications was used. Three pasture management systems (silvopastoral system, rotational system with native regeneration and extensive system) and three evaluation times (08:00 h, 12:00 h, and 16:00 h) were evaluated. After sample collection, dry biomass was determined. In the evaluation of ecophysiological parameters, the photochemical efficiency and estimate of the relative chlorophyll content in brachiaria plants of the three systems were determined. The photochemical efficiency was determined in the grasses of each system, being randomly evaluated three leaves per plant. The silvopastoral system was the one that showed the greatest increase in dry biomass of forage and the best results for the photochemical parameters, standing out as the best system for livestock.